2009
DOI: 10.4314/ajbr.v10i1.48971
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic effect of Vitamin E on the efficacy of artesunate against Plasmodium berghei infection in mice

Abstract: The effect of antioxidant (Vitamin E) on the efficacy of Artesunate was investigated using Plasmodium berghei infected mice. Fifty (50) adult albino mice weighing between 15-25g were used for this study. There were five groups of ten animals each per group. Group I was the normal control group without the parasite and untreated, group II was infected with malaria parasite and 0.9% normal saline was administered, group III was infected with the parasite and treated with artesunate, group IV was infected with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 12 publications
1
12
1
Order By: Relevance
“…There are however, recommendations against administration of vitamin C to patients with malaria, to avoid possible impairment of therapeutic action of antimalarial drugs 8 . This is supported by reports of the interference of antiplasmodial action of antimalarial agents in the presence of antioxidants 9 10 .…”
supporting
confidence: 59%
“…There are however, recommendations against administration of vitamin C to patients with malaria, to avoid possible impairment of therapeutic action of antimalarial drugs 8 . This is supported by reports of the interference of antiplasmodial action of antimalarial agents in the presence of antioxidants 9 10 .…”
supporting
confidence: 59%
“…Therefore, one drug molecule can generate only one free radical [ 34 ]. In vitro [ 25 ] and in vivo [ 35 ] studies showed that this anti-malarial effect of artemisinin was reduced by vitamin E treatment. The additive effect of combination treatment as shown in this study might be caused by the lowering effect of probucol on host plasma vitamin E concentration, which prevented the elimination of free radicals generated by DHA.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, one drug molecule can generate only one free radical [77]. Since anti-malarial effect of artemisinin was seen to be reduced by vitamin E treatment both in vitro [73] and in vivo [78], the beneficial effect of the combination treatment of DHA with probucol [61] might be attributed to the lowering of host plasma concentration of vitamin E by probucol, which prevented the elimination of free radicals generated by DHA. Such a strategy might be applicable to other parasites as well in future, such as trypanosoma [20].…”
Section: A Combination Therapy With Dihydroartemisinin and Probucolmentioning
confidence: 99%